Higher Burden of Cerebral Small Vascular Disease Predicts Major Adverse Cardiac and Cerebrovascular Events and Is Related to Abnormal Blood Pressure Variability Pattern in Hypertension Patients - Xu, Xiaomeng; Huang, Shu; Zeng, YuE; Feng, Yulan; Yue, Dongqi; Shen, Fanxia; Gao, Yang; Zhang, Bei; Yang, Yang; Gu, Lin; Fu, Yi (Frontiers in Aging Neuroscience, 2022)
Background and Objectives: The study aims to test the hypotheses that higher cerebral small vascular disease (CSVD) burden predicts major adverse cardiac and cerebrovascular event (MACCE) in hypertension patients, and that abnormal blood pressure variability (BPV) pattern aggravates total CSVD burden. Methods: We retrospectively reviewed hypertension patients prospectively collected between February 2015 to February 2019 from three participating centers. Patients were included if they had hypertension for over one year and had at least one MRI feature of CSVD. Independent predictors were identified by multivariate logistic regression. Results: Among the 908 patients finally enrolled in the study, the number of CSVD markers (OR, 1.940; 95% CI, 1.393-2.703; P<0.001) independently predicted MACCE with acceptable predictive value (C-statistic: 0.730. 95% CI: 0.669-0.791, P<0.001). Abnormal BPV pattern was identified as an independent risk factor for increased CSVD burden. Among them, reverse-dipper subtype demonstrated the most significant relationship (OR, 1.725; 95% CI, 1.129-2.633; P=0.012). Conclusion: Total CSVD burden independently predicts increased risk of composite MACCE. Abnormal BPV pattern is associated with higher burden of CSVD.